The order of draw of blood specimens into additive containing tubes not affect potassium and calcium measurements. Issue 12 (December 1996) - Majid, A; Heaney, D C; Padmanabhan, N; Spooner, R
Abstract : The effect of order of draw when taking blood into tubes containing additive was investigated in 47 medical inpatients; 12 of these patients acted as a control group. The samples were analysed in the order in which they were withdrawn. The results of potassium and calcium concentrations did not differ significantly between groups. Manufacturers recommend a specific order of draw when taking blood using vacuum based blood collection systems, which are routinely used in many hospitals. The results of this study, however, show that order of draw has no effect on calcium or potassium concentrations.